Quantification of a Novel Photosensitizer of Chlorin e6-C15-Monomethyl Ester in Beagle Dog Plasma Using HPLC: Application to Pharmacokinetic Studies - Xiuxiu Li; Jun Wen; Jingjing Jiang; Xin Zhao; Tingting Zhou; Guorong Fan (Molecules, 2017)
Chlorin e6-C15-monomethyl ester (CMME) is a novel photosensitizer, which is synthetized from the degradation products of silkworm excrement. Preclinical studies on the promising photosensitizer CMME are necessary to determine its therapeutic efficacy and druglikeness. A high-performance liquid chromatography with UV detection (HPLC–UV) method was established for the determination of CMME in beagle dog plasma. The sample preparation involved a protein-precipitation method with acetonitrile after the addition of tanshinone IIA as an internal standard (IS). CMME and the IS were separated on a Diamonsil C18 (2) column (100 mm × 4.6 mm, 5 μm) with a isocratic system of methanol–water containing 20 mM ammonium acetate with 0.3% glacial acetic acid (85:15, v/v). The flow rate was 1.0 mL/min with UV detection using a wavelength of 400 nm. The method was sensitive enough with a lower limit of quantitation (LLOQ) of 0.05 μg/mL and had a good linearity (r2 > 0.999) over the linear range of 0.05–5.00 μg/mL. The intra-day and inter-day accuracies ranged from 98.5% to 102.8% and precisions (RSD) were within 6.8%. The validated method was successfully applied to the pharmacokinetic study of CMME after intravenous administration of single and multiple doses in beagle dogs.